The "money" concept in the dramatic work "One Hundred thousand" by Ivan Karpenko-Karyi (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In the article the features of the nature and content of the concept of «money» in the dramatic work of Ivan Tobilevich «Нundred thousand». The main focus is on revealing definite features of the concept and its functional characteristics, represented within the text of a work of art drama.
Keywords: concept; «money»; drama; stage play